Internal consistency study of EORTC QLQ-C30 and QLQ-PR25 questionnaires for quality of life assessment among prostate cancer patients in a University Hospital, Kuala Lumpur, Malaysia - Norzaher Ismail,; Shamsul Azhar Shah,; Nazarudin Safian,; Syafiq Taib,; Siti Nor Mat, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Prostate cancer is forth most common diagnosed tumors in Malaysian male. The use of a self-reported, quality of life assessment is important for clinical practice, care taker and researcher to evaluate the level of quality of life. The aim of this study was to measure the internal consistency of the translated Malay Language EORTC QLQ-C30 and EORTC PR-25 questionnaires among prostate cancer patient at National University of Malaysia hospital in Kuala Lumpur, Malaysia. Methods This was a cross sectional study conducted between July 2017 and Dec 2017. The respondent comprised of 110 Malaysian prostate cancer patients who were under follow up at Urology and Oncology Clinic. Sets of translated Malay language EORTC QLQ C30 and EORTC PR-25 consisted of functional, symptom and global health status domains were administered to assess their quality of life. Results The translated questionnaires were acceptable by 110 respondents. Cronbach`s α coefficient result were 0.913 (EORTC QLQ-C30) and 0.829 (EORTC PR-25) respectively suggested that this instrument had good internal consistency. Conclusions Our study confirmed that translated Malay language EORTC QLQ-C30 and QLQ-PR25 questionnaires are acceptable, reliable and valid instrument to be used among Malaysian prostate cancer patients.